Influence of temperature and thickness on thin layer drying characteristics of onion (Allium cepa L.) varieties and rehydration capacity - Sobowale, Sunday Samuel (Array, 2020)
Nonlinear regression analysis was conducted for thin layer drying characteristics of two onion varieties (white and red) and some quality characteristics were also examined. The experimental data obtained at drying temperatures of 40, 50, and 60 oC and thicknesses of 2, 4 and 6 mm, was subsequently fitted into four commonly used models (Henderson and Pabis, Lewis, Page, and logarithmic). Moisture diffusivity and activation energy ranged from 8.9 × 10-10 to 8.4 × 10-9 m2/s and 55.98 to 65.68 KJ/mol, respectively. Significant differences (p<0.05) were observed in the colour profile and rehydration ratio. The optimum desirable colour was obtained at 50 oC with 2 mm thick onion slices and the observed higher rehydration ratio indicates good quality of dried onions. Among the four selected drying models, the Page model predicted optimally (R2>0.9) and was found to be better in describing dried onion varieties, while the Lewis model provided the least fit.